2020
DOI: 10.3390/s20020354
|View full text |Cite
|
Sign up to set email alerts
|

Hurdle Clearance Detection and Spatiotemporal Analysis in 400 Meters Hurdles Races Using Shoe-Mounted Magnetic and Inertial Sensors

Abstract: This research aimed to determine whether: (1) shoe-worn magnetic and inertial sensors can be used to detect hurdle clearance and identify the leading leg in 400-m hurdles, and (2) to provide an analysis of the hurdlers’ spatiotemporal parameters in the intervals defined by the hurdles’ position. The data set is composed of MIMU recordings of 15 athletes in a competitive environment. The results show that the method based on the duration of the flight phase was able to detect hurdle clearance and identify the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
(36 reference statements)
3
14
1
Order By: Relevance
“…The current document answers the comment addressed by Schmidt, M., Nolte, K., Alt, T., and Jaitner, T. regarding our recent paper "Hurdle Clearance Detection and Spatiotemporal Analysis in 400 Meters Hurdles Races Using Shoe-Mounted Magnetic and Inertial Sensor" (Sensors 2020, 20, 354) [1].…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…The current document answers the comment addressed by Schmidt, M., Nolte, K., Alt, T., and Jaitner, T. regarding our recent paper "Hurdle Clearance Detection and Spatiotemporal Analysis in 400 Meters Hurdles Races Using Shoe-Mounted Magnetic and Inertial Sensor" (Sensors 2020, 20, 354) [1].…”
Section: Introductionsupporting
confidence: 57%
“…The range of speeds observed in [1] was greater than for the validation study [2]; therefore, we could not obtain the actual bias at the observed running speeds.…”
mentioning
confidence: 88%
See 3 more Smart Citations